Development of textbooks to support merdeka curriculum learning on nanotechnology material for Phase E - Ildyra Fazira; Mawardi Mawardi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The development of a textbook to support Merdeka curriculum learning on nanotechnology material for phase E high school students is equipped with more detailed material content, multi representations that are easy to understand, and a more attractive book display. It is hoped that it can increase students' learning motivation and abilities due to learning loss due to COVID-19 and support the learning process and education in the era of the industrial revolution 4.0. Ministerial Decree of The Minister of Education and Culture of The Republic of Indonesia No.008/H/KR/2022 concerning chemistry learning outcomes in phase E high school students there is nanotechnology material. This study aimed to develop a valid and practical textbook to support learning for the Merdeka curriculum on phase E nanotechnology material. Research in modern chemistry continues to grow, evidenced by the discovery of nanotechnology, which involves measuring and manipulating matter at the atomic, molecular, and supramolecular levels measured on a scale of 1-100 nm. The research conducted is categorized as an educational design study using the Plomp development model and includes three phases: preliminary research, development or prototyping, and evaluation. Validation analysis resulted in a content effectiveness test score 0.91 for one valid category. At the same time, teacher and student practice tests scored 92% and 92%, respectively, in the highly practical practicality category. In summary, it is effective and practical to develop a textbook for Phase E high school students to support learning the Merdeka curriculum on nanotechnology material.